Effect of Aqueous Extract of Unripe Linn on Parameters Affecting Reproduction in Rats - Collins Azubuike Onyeto PhD; Akachukwu Marytheresa Onwuka MS; Ikechukwu Emmanuel Peter MS; Chukwuemeka Sylvester Nworu PhD; Peter Achunike Akah PhD (SAGE Publishing, 2024)
Objective Aqueous extract of unripe Musa paradisiaca fruit is commonly used for the treatment of ulcers in eastern Nigeria. This study aimed to assess the acute and subacute effects of an aqueous extract of unripe fruit on male and female fertility in rats. Methods Aqueous extracts obtained by maceration were analyzed for acute and subacute toxicity and for the presence of phytochemical constituents using standard procedures. The extract (100, 500, and 1000 mg/kg) was administered daily to rats of both sexes for 28 d. Blood samples collected on days 0 and 28 were assessed for follicle-stimulating hormone (FSH), luteinizing hormone (LH), catalase (CAT), superoxide dismutase (SOD), and malondialdehyde (MDA). Testes and ovaries were harvested for histopathological analysis. Sperm were also collected to determine the sperm count and motility. Results Phytochemical screening revealed the presence of saponins, tannins, alkaloids, and resins. After an oral dose of up to 5000 mg/kg, there were no deaths in the acute toxicity test. The extract (500 mg/kg) significantly ( P  < .05) enhanced sperm count and motility relative to the untreated control; significantly ( P  < .05) reduced SOD, CAT, and glutathione levels, while significantly ( P  < .05) elevated LH, FSH, and MDA levels in male and female rats. Histological examination revealed significant structural damage to the ovaries. Conclusion Unripe Musa paradisiaca fruit exhibited an adverse toxicological profile following prolonged administration and caused oxidative stress in rodents.